PENGARUH METODE ROLE PLAYING TERHADAP KEMAMPUAN SOSIO-EMOSIONAL ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN MANDIRI KABUPATEN MAMUJU TENGAH - Rima Nabila; Abdul Saman; Muhammad Yusri Bachtiar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) determine the description of socio-emotional abilities in children before and after implementing activities using the role playing method, 2) determine the description of the application of the role playing method on the socio-emotional abilities of children aged 5-6 years, 3) determine the effect of the method role playing on the socio-emotional abilities of children aged 5-6 years in group B at KB Mandiri, Central Mamuju Regency. This research design is a quasi experimental design. The data collection techniques used in this research are observation and documentation. The subjects of this research were 20 children divided into 2 groups, namely a control group of 10 children and an experimental group of 10 children. The results of the research show that: 1) the socio-emotional abilities of children aged 5-6 years before being given treatment in the experimental group and control group were generally in the medium category or starting to develop, then the socio-emotional abilities of children aged 5-6 years in the experimental group and the control group at KB Mandiri, Central Mamuju Regency, after being given treatment, was generally in the high category or developing according to expectations, 2) the application of the role playing method at KB Mandiri, Central Mamuju Regency, namely with the following steps: children were given toys in the form of doctor's equipment, then children are asked to choose a role according to their preferred profession, before playing the game the researcher gives the rules and tells how to play, after that the child is given the opportunity to start the game with other children waiting their turn, 3) The results of the data analysis obtained can be seen in the results which show that the value obtained from the activities that have been carried out with a value of Asymp Sig (2-tailed) 0.005, meaning that there is an influence of the role playing method on children's socio-emotional abilities.